Moderasi Corporate Governance terhadap Faktor-Faktor yang Mempengaruhi Agresivitas Pajak pada Sektor Energi - Sirait, Asnat; Harefa, Nursaida (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
tax aggressiveness in energy sector enterprises traded on the Indonesia Stock Exchange, in which corporate governance serves as a moderating factor. This research analyzes the effect of firm size, profitability, leverage, capital intensity, and inventory intensity on tax aggressiveness. Tax aggressiveness is measured using indicators previously applied in past studies. The results indicate that profitability has a positive but insignificant effect, leverage has a positive and significant effect, and inventory intensity also has a positive and significant effect on tax aggressiveness. Meanwhile, firm size has a negative and significant effect, and capital intensity has a negative and significant effect on tax aggressiveness. Furthermore, the moderation analysis shows that corporate governance significantly moderates the relationship between firm size, profitability, capital intensity, and inventory intensity on tax aggressiveness. However, the interaction between corporate governance and leverage does not significantly moderate the effect on tax aggressiveness. All tests were conducted using empirical data obtained from publicly available financial reports and analyzed through multiple linear regression methods with appropriate statistical approaches